Synthesis and properties of neat, hybrid, and copolymeric polyamide 12 microparticles and composites on their basis - Dencheva, Nadya Vasileva (2022)
Neat and hybrid polyamide 12 (PA12) based powders are important raw materials for additive manufacturing. This study describes a facile method for the synthesis of pure, hybrid and copolymeric microparticulate materials based on one-pot activated anionic ring-opening polymerization (AAROP) of laurolactam in solution. The results reveal the possibility to obtain in good yields, for reaction times of 2 h and temperatures of up to 110 ºC neat and hybrid PA12 microparticles (MP) carrying metal or carbon fillers. CopolymericPA12/PA6 MP can also be successfully prepared. All MP materials are analyzed by spectral, microscopy, thermal, and synchrotron X-ray scattering methods in order to clarify their morphology, chemical and crystalline structure, melting and degradation behavior. The melting temperature of the PA12MP is lower than of the commercial PA12, the presence of metal particles with PA6 additionally decrease it well below 170ºC. The composites prepared by compression molding of PA12 MP display elastic modulus of up to 1.49 GPa, the stresses at yield and break reaching 50 and 69 MPa, respectively. It is concluded that the neat, hybrid, and copolymeric pulverulent materials obtained via microencapsulation by AAROP in solution may be useful in additive manufacturing processing.